Evaluation of the physicochemical and biochemical composition of biol enriched with different concentrations of alperujo - Casanova Pavel, David; Estación Experimental Agraria Tacna. Dirección de Recursos Genéticos y Biotecnología, Instituto Nacional de Innovación Agraria, Av. Collpa S/N La Agronómica, distrito Coronel Gregorio Albarracín Lanchipa, Tacna (2021)
Sustainable agroecological practices make it possible to reduce the negative environmental and socio-economic impact on agriculture. Among these practices, is the use of composts and biol found as fertilizers, fertilizers or organic amendments with an effectiveness, in many cases, higher than that exerted by natural manures. In this context, the agri-food industry generates a great variety and quantity of waste and by-products, which can potentially be used as fertilizers and soil amendments due to their high content of organic matter and plant nutrients. Therefore, the objective of the present investigation was to evaluate the physicochemical and biochemical composition of the biol with five different concentrations of alperujo (5, 10, 15, 2 and 25%). The unidirectional analysis of variance of the results obtained in the concentration of organic matter, organic carbon, phosphates, phenols, nitrates and protein did not show a significant statistical difference, however, the authors recommend the concentration of alperujo 25% due to presenting the lower concentration of phenols and high concentration of organic matter.